Post-Construction Analysis of Scale and Proportion: A Case Study of the Woodbury Towers, USA, in Reflecting Cogent Design Principles - Worasak Luangsuwan (My University, 2023)
Critically assessing your own design work after it has been constructed for several years is an exciting question of self-peer review that has to set aside the initial design amplitude while letting the theories perform in order to discover some unexpected results with respect to the original design. This paradoxical mechanism between practicing and teaching when career switching from a professional practitioner to a university instructor can harmoniously integrate theory and praxis to illuminate future paths and amplify innovation. Here, I use the Woodbury Towers in the Woodbury Irvine Community as a case study to explore planning design practice in context of the Southern California landscape as the subject of the self-peer review process. Creating community is building a place for people to live and share their experience. Community basically refers to sets of people who may identify themselves with a place in terms of notions of commonality, shared values or solidarity in particular contexts. Landscape architecture can contribute to a sense of community by contributing theories, experiences and design vision in the development process. In this paper, the synchronization of design scale and proportion considered essential, has been explored to reflect theoretical functions and aesthetic characteristics of good design since the Classical Era. The principle of The Golden Section ratio simulated with a digital superimposition technique is the main tool for this research method which led to discovery of the subconscious ideas in the post-construction phase.
Keywords: CLARITY; Subconscious; Architecture and Computational Design